Method and appraisal in the physical sciences the critical background to modern science, 1800-1905 - Howson, Colin (Cambridge University Press, 1976)
First published in 1976, this is a volume of studies on the problems of theory-appraisal in the physical sciences - how and why important theories are developed, changed and are replaced, and by what criteria we judge one theory an advance on another. The volume is introduced by a classic paper of Imre Lakatos's, which sets out a theory for tackling these problems - the methodology of scientific research programmes. Five contributors then test this theory against particular and celebrated case-studies in the history of the physical sciences (particularly in the nineteenth century). The volume ends with a characteristically forceful and original critique of the whole enterprise by Paul Feyerabend. the book is a companion volume to Method and Appraisal in Economics. Both are natural sequels to Criticism and the Growth of Knowledge and attempt to work out in particular cases the implications of some of the theories presented in that book